SMN1 c.5C>G (p.Ala2Gly) missense variant, a challenging molecular SMA diagnosis associated with mild disease, preserves SMN nuclear gems in patient-specific fibroblasts - Cook, Sara L.; Stout, Christian; Kirkeby, Lindsey; Vidal-Folch, Noemi; Oglesbee, Devin; Hasadsri, Linda; Selcen, Duygu; Milone, Margherita; Anderson, Daniel; Staff, Nathan P. (Frontiers in Genetics, 2024)
Introduction Spinal muscular atrophy (SMA) is caused by homozygous loss of the SMN1 gene with SMN2 gene copy number correlating with disease severity. Rarely SMA is caused by a deletion on one allele and a pathogenic variant on the other. The pathogenic missense variant c.5C>G (p.Ala2Gly) correlates with a milder disease phenotype that does not correlate with SMN2 copy number. In a mouse model the c.5C>G transgene produces SMN that is thought to form partially functional SMN complexes, but levels in humans have not yet been investigated. Methods We identified two patients with mild SMA caused by a heterozygous deletion of SMN1 and the heterozygous variant, c.5C>G. Molecular findings were confirmed with deletion duplication testing and Sanger sequencing. Skin fibroblasts were collected and cultured, and SMN expression was analyzed using immunofluorescence. Results Two patients with slowly progressing mild weakness were confirmed to have heterozygous pathogenic missense variant c.5C>G and a heterozygous deletion of SMN1. Their clinical presentation revealed much milder disease progression than patients with matched SMN2 copy number. Analysis of the patient’s fibroblasts revealed much higher numbers of SMN nuclear complexes than a patient with a homozygous SMN1 deletion and matched SMN2 copy number. Conclusions These case reports reinforce that the rare c.5C>G variant causes mild disease. Furthermore, the analysis of SMA nuclear gems in patient samples supports the theory that the p.Ala2Gly SMN can form partially functional SMN complexes that may carry out essential cellular functions and result in milder disease.